Mindfulness-based music therapy for mental health in senior college students: a randomized controlled trial - Wang, Long; Zhang, Xiaoyan; Pan, Lei; Guo, Rui (Frontiers in Psychology, 2025)
BackgroundSenior college students face a heightened risk of mental health problems, indicating the need for effective interventions. Mindfulness-based music therapy (MBMT) has been shown to improve mental health outcomes across various populations, yet evidence of its effectiveness in senior college students remains scarce. This randomized controlled trial aimed to test the efficacy of MBMT in improving mental health among senior college students.MethodsFrom September 2024 to December 2024, 400 senior college students were recruited and randomly assigned to the intervention group (n = 200) or the control group (n = 200). The intervention group received six weekly 40-min MBMT sessions, along with assigned homework, over 6 weeks. The primary outcomes included depression and anxiety, while the secondary outcomes included obsessive-compulsive symptoms, sleep quality, and resilience, which were assessed pre- and post-intervention.ResultsA total of 181 students (adherence rate: 90.50%) in the intervention group and 197 students (adherence rate: 98.50%) in the control group completed the intervention and pre- and post-assessments. At baseline, the MBMT group and the control group showed no significant differences in sample characteristics and mental health indicators. Following the intervention, all mental health indicators in the MBMT group improved significantly and remained stable in the control group. The MBMT group demonstrated significantly lower levels of depression, anxiety, and obsessive-compulsive symptoms, as well as higher levels of sleep quality and resilience, compared to the control group post-intervention.ConclusionMBMT is effective in decreasing depression, anxiety, and obsessive-compulsive symptoms and improving sleep quality and resilience among senior college students. Our findings suggest that MBMT may be incorporated into the curriculum for senior college students to enhance their mental health and general well-being.